PERANCANGAN ULANG USER INTERFACE APLIKASI SUPERCONSIGN DENGAN METODE HUMAN CENTERED DESIGN - Fonda, Surya; Musdar, Izmy Alwiah; Adys, Himala Praptami (KHARISMA Tech, 2023)
This study aims to redesign the User Interface (UI) of the SuperConsign application using the Human-Centered Design method as a solution to enhance user comfort and satisfaction. The study involved 20 participants from the general public who have experience purchasing second-hand items and using second-hand sales applications to demonstrate the effectiveness of the Human-Centered Design method in creating a better user experience and improving the potential of the SuperConsign application in the market. The method comprises three main stages: inspiration, ideation, and implementation. Through observation and analysis of issues with the SuperConsign application, the study resulted in a better and more user-friendly UI redesign. The result of the study revealed a significant increase in usability scores from 38 to 76.5 based on the System Usability Scale (SUS). It can be concluded that SuperConsign is better and more user friendly after UI redesigning.